Natural Gas Engine Technologies: Challenges and Energy Sustainability Issue - Chala, G. T.; Abd Rashid, Abd Aziz; Hagos, F. Y. (MDPI AG, 2018)
Energy sustainability and environmental issues pose greater challenges on different primary energy sectors as the global energy demand increases and it is projected to further increase with an upsurge in population. On the other hand, energy sources from conventional fossil-based fuels are depleting, forcing explorations in challenging and difficult locations. As a result, the use of alternative fuels received dramatic consideration to substitute these conventional fuels, of which natural gas took the significant share. However, the share of natural-gas vehicles in the current vehicle market is quite small, and it is estimated to be below 5%. This paper reviews the current resource scenarios including proven and potential reserves, current production, and consumption, along with the fueling infrastructure, distribution, and storage. It also provides summary of the development of fuel-injection technologies aimed to enhance the performance of gas engines. More attention was also given to natural-gas engines and their limitations. Parameters affecting the performance and combustion of compressed natural gas (CNG) in spark-ignition (SI) engines are thoroughly assessed, among which compression ratio and injection timing play major roles in the optimization of CNG-fueled engines. Furthermore, different technologies that help close the performance gap between conventional liquid-fuel and natural-gas engines and future directions of the research are presented